2019
DOI: 10.1002/ptr.6596
|View full text |Cite
|
Sign up to set email alerts
|

Diosmetin exhibits anti‐proliferative and anti‐inflammatory effects on TNF‐α‐stimulated human rheumatoid arthritis fibroblast‐like synoviocytes through regulating the Akt and NF‐κB signaling pathways

Abstract: Rheumatoid arthritis (RA) is a chronic inflammatory disease characterized by inflammation and proliferation of synovial tissues. Diosmetin is a bioflavonoid possessing an anti‐inflammatory property. Herein, we aimed to study the effects of diosmetin on the inflammation and proliferation of RA fibroblast‐like synoviocytes MH7A cells. MH7A cell proliferation was measured using cell counting kit‐8 assay. Cell apoptosis was examined using flow cytometry. The production of inflammatory cytokines including interleuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 44 publications
(45 reference statements)
1
30
0
Order By: Relevance
“…Diosmetin is a type of common flavonoids. It is rich in citrus fruits, olive leaves and extracts from common herbs in southern China with a variety of functions such as scavenging free radicals, anti-inflammatory and anti-oxidative stress [ 13 15 ]. Recently, it is shown that diosmetin has anti-tumor effect by inhibiting the cell proliferation, inducing cell apoptosis and regulating cell cycle on breast cancer cells, liver cancer cells, colon cancer cells, leukemia cells and other tumors, indicating it is a potential promising treatment for cancers [ 17 , 18 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diosmetin is a type of common flavonoids. It is rich in citrus fruits, olive leaves and extracts from common herbs in southern China with a variety of functions such as scavenging free radicals, anti-inflammatory and anti-oxidative stress [ 13 15 ]. Recently, it is shown that diosmetin has anti-tumor effect by inhibiting the cell proliferation, inducing cell apoptosis and regulating cell cycle on breast cancer cells, liver cancer cells, colon cancer cells, leukemia cells and other tumors, indicating it is a potential promising treatment for cancers [ 17 , 18 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…RA FLS with TNFα stimulation was widely served as an in vitro model to explore RA pathogenesis and screen potential therapeutic drugs. 22,23 In this study, we evaluated the effects of lentivirus-mediated AQP1 overexpression or silencing on the proliferation, apoptosis, migration and invasion of TNF-αstimulated MH7A cells, and revealed the underlying mechanisms related to Wnt/β-catenin signaling pathway. Aggressive proliferation of RA FLS has been suggested to contribute to synovial hyperplasia, the basic pathological feature of RA.…”
Section: Discussionmentioning
confidence: 99%
“… 7 At present, MH7A cells as a mature pathological model cells have been widely used in the study of RA. 2 , 8 , 9 Human rheumatoid arthritis fibroblast-like synovial cell line of MH7A was obtained from the Beina Biological Company (Beijing, China), sub-cultured in DMEM (high glucose) containing 10% FBS at 37°C. Cells were passed through every 3–4 days, and only 3–5 generations of MH7A cells were used in the experiment.…”
Section: Methodsmentioning
confidence: 99%